PHARMACOGNOSTIC PROFILE AND PHYTOCHEMICAL INVESTIGATION OF SYZYIUM CUMINI BARK EXTRACTS - MOHAMMED RAFIQKHAN; VIJITHA VISWAMBHARAN (International Journal of Pharma and Bio Sciences, 2015)
Knowledge of herbs has been handed down from generation to generation for thousands of years. Herbal drugs constitute a major part in all traditional systems of medicines. Plants above all other agents have been used for medicine from time immemorial because they have fitted the immediate personal need and are easily accessible and inexpensive. The medicinal plants find application in pharmaceutical, cosmetic, agricultural and food industry. In last few decades, Syzyium cumini is extensively studied for its medicinal properties by advanced scientific techniques and a variety of bioactive compounds have been isolated from the different parts of the plant and were analysed pharmacologically. In our present investigation, pharmacognostic profile and phytochemical screening of Syzyium cumini bark has been evaluated for the presence of bioactive compounds. The study revealed the presence of alkaloids, flavonoids, terpenoids, phenolic compounds, sterols, carbohydrates, glycosides and tannins. The results suggest that methanolic extract of Syzyium cumini bark has promising therapeutic potential, its pharmacological properties which if properly harness can be used in the management of various diseases and can serve as a base for the development of novel potent drug in ethomedicine.